Novelty during rearing increased inquisitive exploration but was not related to early ranging behavior of laying hens - Taylor, Peta S.; Campbell, Dana L. M.; Jurecky, Emma; Devine, Natalie; Lee, Caroline; Hemsworth, Paul H. (Frontiers in Animal Science, 2023)
Range use by free-range laying hen flocks is heterogeneous. We hypothesized that ranging behaviour may be motivated by curiosity and thwarted by fearfulness. This project aimed to increase a hen’s motivation to explore by enriching the rearing environment and identify relationships between exploration, fear and ranging. Day-old Hy-Line chicks (n = 1700) were reared in environments that provided novel items, structures for perching or an industry standard floor rearing environment. Prior to range access, fear and exploratory behaviors were assessed at 18 weeks of age (cohort 1; n = 30 hens/treatment) via novel arena and novel object tests and at 22 weeks of age (cohort 2; n = 30 hens/treatment) using an 8-arm radial maze choice paradigm adapted from previous rodent research. Hens were trained to expect success in two arms (reward) and failure in two arms (mild punishment), the remaining four arms (ambiguous arms) were not available during training. After training, all hens were retested for 8 minutes with access to the four familiar arms only, then for four minutes with access to the ambiguous arms for the first time, in addition to the success and failure arms. Latency to enter the ambiguous arms and the number of ambiguous arms entered were assessed as an indicator of a hen’s willingness to forgo reward and risk punishment to explore a novel area. At 25 weeks of age, hens were provided with range access and individual range access was monitored for three weeks. Latency to access the range and the number of days the range was accessed was not related to rearing treatment (p > 0.05) and was only weakly correlated with behavior during the novel arena, novel object and 8-arm radial maze tests (r < 0.3). However, hens reared in the novelty rearing environment were more willing to forgo reward to explore the ambiguous arms than hens reared in the control environment (p = 0.004). We did not identify strong evidence that exploration or fearfulness was related to early ranging behavior. However, we show that motivation to explore increases when hens are reared in an enriched environment.